PENGARUH PROGRAM DESA MANDIRI PANGAN TERHADAP TINGKAT PENDAPATAN PETANI JAGUNG - Sasmita Siregar; Armansyah ,; Syafrina Dewi (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2012)
AbstractThe research conducted using the case study method (Case Study). Results of hypothesis testing using multiple linear regression R-square of 0.82 which indicates that it simultaneously (synchronously) no significant effect between capital and labor to the income level of farmers' maize affect the rest of 82% is influenced by other variables outside of variables studied. From the test results were statistically obtained multiple R value of 0.90% means that overall there is a close relationship between capital and labor to the income level of farmers' maize is supported by the F-calculated value is greater than the F-table at the level of 95 % (0.05 α). Partially no effect on the level of capital income of corn farmers with value t count> t-table of the 95% confidence level.While labor has no effect on the level of income of corn farmers. Implementation of the program was to improve the welfare of the community, especially at the level of farmers' income has gone well according to the needs of farmers in the village. Test results with an average difference test found that the level of income disparity between village farmers who participate in food security programs and income of farmers who do not follow the food security program of the Village 17.23 t count> t-table of 2.04 at level 95 %